2020
DOI: 10.1111/1460-6984.12542
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing Parent Led Therapist Supervised Articulation Therapy (PLAT) with routine intervention for children with speech disorders associated with cleft palate

Abstract: Background A total of 68% of pre‐school children with cleft palate have speech problems requiring speech therapy. There is a lack of access to regular targeted therapy. Parent training leads to positive outcomes in early communication skills in cleft palate and non‐cleft speech disorders. Connected health has been used to address inadequate access to therapy, providing intervention to those who would not otherwise receive therapy. Aims To evaluate the speech, activity and participation outcomes of Parent Led, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…Nineteen studies contributed with IPD on speech production. As a rough overview of these studies, the therapy was implemented in the form of intensive summer camps in three studies (Pamplona et al, 2014(Pamplona et al, , 2017Van Demark & Hardin, 1986), the SLT was implemented in the form of conventional clinical care in four studies (Derakhshandeh et al, 2016;Pamplona & Ysunza, 2018;Roxburgh et al, 2016;Sweeney et al, 2020), the therapy was implemented through an initial short workshop led by SLTs and then carried out by parents or speech assistants over a long duration in nine studies (Dobbelsteyn et al, 2014;Hanchanlert et al, 2015;Makarabhirom et al, 2015;Prathanee, 2011;Prathanee et al, 2014Prathanee et al, , 2020Pumnum et al, 2015;Scherer et al, 2008;Sritacha et al, 2016), and the therapy was very brief in three studies (Alighieri et al, 2019;Lindeborg et al, 2020;Luyten et al, 2016). See Table 1 for a general overview of these studies, and see Table 2 for risk of bias assessment of these studies.…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
“…Nineteen studies contributed with IPD on speech production. As a rough overview of these studies, the therapy was implemented in the form of intensive summer camps in three studies (Pamplona et al, 2014(Pamplona et al, , 2017Van Demark & Hardin, 1986), the SLT was implemented in the form of conventional clinical care in four studies (Derakhshandeh et al, 2016;Pamplona & Ysunza, 2018;Roxburgh et al, 2016;Sweeney et al, 2020), the therapy was implemented through an initial short workshop led by SLTs and then carried out by parents or speech assistants over a long duration in nine studies (Dobbelsteyn et al, 2014;Hanchanlert et al, 2015;Makarabhirom et al, 2015;Prathanee, 2011;Prathanee et al, 2014Prathanee et al, , 2020Pumnum et al, 2015;Scherer et al, 2008;Sritacha et al, 2016), and the therapy was very brief in three studies (Alighieri et al, 2019;Lindeborg et al, 2020;Luyten et al, 2016). See Table 1 for a general overview of these studies, and see Table 2 for risk of bias assessment of these studies.…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
“…More specifically, parents found it important to receive information regarding the transfer of learned skills to the home environment which suggests that they are eager to learn techniques to enhance generalization. Sweeney et al (2020) compared the effect of a parent-led therapist-supervised (PLAT) speech intervention with the effect of routine speech intervention in children with a CP±L. Parents allocated to the parent-trained group followed a 2-day training course including lectures, speech samples and quizzes.…”
Section: Discussionmentioning
confidence: 99%
“…Speech and language therapy interventions for children with CP±L typically involve direct therapy with a speech and language therapist with follow-up activities for parents to complete at home (Bessell et al, 2013;DeVeney et al, 2017). While the involvement of parents in speech intervention is not new, it has become more of a feature of therapy for children with CP±L, with many using technology to assist in this process (Sweeney et al, 2020). This is sensible given the evidence that parents can be trained to deliver naturalistic intervention techniques for children with non-cleft related speech and language disorders (Kaiser & Hancock, 2003;Kaiser & Hester, 1994) and that parent participation can yield better therapy outcomes for language skills than clinician led interventions (Pamplona & Ysunza, 2000).…”
Section: Facilitator Of Early Interventionmentioning
confidence: 99%
“…For example, Sugden et al (2016) suggested that parent involvement in interventions for children with speech sound disorder is possible and can be effective. Furthermore, a study by Sweeney et al (2020) provided evidence that parents can be trained to carry out speech articulation therapy at home for a child with CP±L and suggested that this can be an alternative method of speech and language therapy service delivery. However, it is important to reflect that the impact of parent-implemented intervention may be dependent on family dynamics and different situations and therefore may not be a reliable or suitable service for all children (Sugden et al, 2016).…”
Section: Facilitator Of Interventionmentioning
confidence: 99%